2009
DOI: 10.1016/j.ejcnurse.2009.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences and Concerns of Young Adults (18–40 Years) Living with an Implanted Cardioverter Defibrillator (ICD)

Abstract: These data reveal that young adults with ICDs experience the unique concerns of childbearing, childrearing, and are worried about their financial security. These findings provide insight for the development of age-appropriate interventions for young adults before and after ICD implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 34 publications
4
58
0
Order By: Relevance
“…This is because phantom shocks were predominantly encountered during sleep or sleep-wake transitions with rarer instances while awake [37]. By comparison, although some participants recalled experiencing physical symptoms of nausea, warmth, dizziness, and altered heart rhythm preceding objective shocks [20, 38], the majority were unable to foresee the impending shocks [38]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because phantom shocks were predominantly encountered during sleep or sleep-wake transitions with rarer instances while awake [37]. By comparison, although some participants recalled experiencing physical symptoms of nausea, warmth, dizziness, and altered heart rhythm preceding objective shocks [20, 38], the majority were unable to foresee the impending shocks [38]. …”
Section: Resultsmentioning
confidence: 99%
“…Common terms consisting of ‘explosion’, ‘blow’, ‘bomb’, ‘shot by gun’ [20, 23, 30], or terms with close associations like ‘thunder’ [23], ‘lightning’ [30, 38], and even phrases of similar meanings like ‘electric shock’ [38] and ‘sticking your finger in the light socket’ [23] illustrated the suddenness, striking, and high impact nature of objective shocks. Partners in close body contact with the participants also reported feeling a sudden repulsive force of being ‘kicked’ or ‘thrown’ which corroborated with the participants’ account of experiencing objective shocks [23].…”
Section: Resultsmentioning
confidence: 99%
“…McDonough 44 examined a sample of young (18-to 40-year-old) patients and found that some individuals experienced anxiety during exercise because of the potential for an ICD shock. 44 Interestingly, some individuals chose to reduce their level of exercise, despite physician advice permitting participation, because of fear of an ICD shock. Other studies have reported similar results, reporting that a fear of exercise is common among ICD patients and that this fear negatively influences quality of life.…”
Section: Exercise Recommendations For Patients With Implantable Cardimentioning
confidence: 99%
“…46,47 These studies highlight the importance of how we negotiate the most effective ways to communicate the risks and benefits of exercise to this patient group, so that they can safely gain quality of life improvements. 44,45 The effect of functional capacity and general fitness on adjustment and anxiety levels of ICD patients has also been examined. In a sample of ARVC patients with an ICD, a reasonably good level of functional capacity (ie, ability to participate in activities, such as daily living, sports, recreational activities) was observed overall.…”
Section: Exercise Recommendations For Patients With Implantable Cardimentioning
confidence: 99%
See 1 more Smart Citation